Structural and Functional Evaluation of Road Pavement on Jalan Raya Ligung, Majalengka - Yoga Setyawan; Mulia Pamadi (LEADER: Civil Engineering and Architecture Journal, 2024)
Assessing road pavement's structural and functional characteristics is essential for managing global transportation infrastructure. This study evaluates the pavement on Jalan Raya Ligung, Majalengka, using advanced technologies such as sensors and predictive data analytics for real-time monitoring. Implementing predictive models and sensors allows for early road damage detection, facilitating efficient and timely repairs. The study also emphasizes the significance of effective drainage systems to address unstable weather conditions caused by climate change, ensuring the durability and safety of road infrastructure.Heavy traffic loads greatly influence the durability and reliability of road pavements. Commercial trucks and other heavy vehicles accelerate pavement wear. Therefore, selecting appropriate materials and structural designs is crucial. Evaluating the current condition of roads and their maintenance history provides insights into the types of interventions performed, their frequency, and associated costs. The trend towards data-driven preventive maintenance helps identify potential issues early on.The research methodology involved surveying 24 respondents to assess the road pavement quality in Jalan Raya Ligung, Majalengka. The survey revealed that most road users are male motorcycle riders. The evaluation covered surface smoothness, layer thickness, structural strength, and drainage capability. The findings showed an average importance score of 2.93% and a satisfaction score of 2.06%. The study concludes that proper surface layer design is vital for better ride quality and safety. Effective maintenance management is necessary to ensure that road infrastructure remains optimal, supporting mobility and local economic activities.This research offers a comprehensive understanding of the challenges and potential solutions related to road infrastructure and driver safety in the region, providing a solid foundation for more effective policy recommendations in road management and maintenance.